2020
DOI: 10.1155/2020/5764195
|View full text |Cite
|
Sign up to set email alerts
|

Nonexistence of Global Weak Solutions of a System of Nonlinear Wave Equations with Nonlinear Fractional Damping

Abstract: We consider the system of nonlinear wave equations with nonlinear time fractional damping utt+−Δmu+CD0,tαtσuq=vp,t>0,x∈ℝN,vtt+−Δmv+CD0,tβtδvr=vs,t>0,x∈ℝN,u0,x,ut0,x=u0x,u1x,x∈ℝN,u0,x,ut0,x=u0x,u1x,x∈ℝN,where u,v=ut,x,vt,x, m and N are positive natural numbers, p,q,r,s>1, σ,δ≥0, 0<α,β<1, and  CD0,tκ, 0<κ<1, is the Caputo fractional derivative of order κ. Namely, sufficient criteria are derived so that the system admits no global weak solution. To the best of our knowledge, the considered sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…More recently, Jleli, Kirane, and Samet 7 studied the system utt+false(normalΔfalse)mu+𝔻0false|tαfalse(tσfalse|ufalse|pfalse)=false|vfalse|q,vtt+false(normalΔfalse)mv+𝔻0false|tβfalse(tδfalse|vfalse|rfalse)=false|ufalse|s, where 0<α,β<1,p,q,r,s>1; they showed that under certain conditions, solutions blow‐up in a finite time.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Jleli, Kirane, and Samet 7 studied the system utt+false(normalΔfalse)mu+𝔻0false|tαfalse(tσfalse|ufalse|pfalse)=false|vfalse|q,vtt+false(normalΔfalse)mv+𝔻0false|tβfalse(tδfalse|vfalse|rfalse)=false|ufalse|s, where 0<α,β<1,p,q,r,s>1; they showed that under certain conditions, solutions blow‐up in a finite time.…”
Section: Introductionmentioning
confidence: 99%